ANALISIS KINERJA PEGAWAI TAMAN MARGASATWA KOTA SEMARANG - Aldini Novana Putri; Fitriyah .; Turtiantoro . (Journal of Politic and Government Studies, 2014)
AbstractTourism is one of the activities that support the economy and a potential source of income for a region. Tourism spots / recreations are a symbol of the presence of tourism activity itself. Semarang city has some attractions that are able to be a mainstay and a place for people to unwind. Among the tourism spots which become the mainstay of Semarang is the Wildlife Park of Semarang. Semarang Wildlife Park offers amusement or recreation that is able to attract the attention of the public to always re-visit the place. Public interest to always return to the Wildlife Park Semarang must be followed by the performance of the staff of the Wildlife Park to always provide the best service to the community.The method used by the author is a qualitative research method with descriptive analytic approach. Used data collection technique is data triangulation consisting of interviews, observation and documentation. The data analysis technique used by the author is an interactive analysis technique which is supported by the documents that author gets in the locus of research.Research conducted by the author is the analysis of the performance of employees in Wildlife Park of Semarang. The author found a lack of good governance in the management of Semarang Wildlife Park, one of the reason is the performance of the staff of the Wildlife Park which is still less than satisfactory. This can occur due to several factors such as inhibiting the lack of facilities and infrastructure support, as well as the lack of cash injection from the Government ofSemarang which can be an important element in improving the management of Semarang Wildlife Park itself, and the absence of the wildlife conservation license due to its management should not be from government agencies but must go through the local company. Conclusion of a study conducted by the author that the presence of Wildlife Park of Semarang contributes substantially to the Local Revenue of Semarang, but on the other hand the performance of employees of Wildlife Park of Semarang still insatisfactory in service delivery due to several factors such as lack of inhibiting one quality of human resources contained in the Wildlife Park of Semarang. The author recommends that with the proliferation of creative economic activities that can provide a positive injection to the scope of the Semarang Wildlife Park itself as well as the search for a third party or partner from the private sector are able to fund and develope Semarang Wildlife Park to be able to compete with Wildlife Park in other cities. Keyword : Tourism, Employees Performance, Operational Office Unit of Semarang Wildlife Park